Toponyms in the Slavonic Excerpt from the Chronicle of Julius Africanus - Totomanova, Anna-Maria (Studia Ceranea, 2024)
For a long time, Julius Africanus’ Chronicle has only been known through hundreds of fragments scattered across Greek, Latin and Oriental (Syriac, Arabic, and Armenian) manuscripts. About fifteen years ago, a long and coherent Slavonic excerpt from Africanus’ Chronicle was found in a chronographic compilation that survives in the five Russian witnesses of the 15th–16th centuries. The compilation has been erroneously identified as a Slavic translation of an abridged version of the Chronicle of George Synkellos. The excerpt contains Africanus’ main narrative devoid of the pre-Olympic history of nations except for the history of the Judeans. Taking up about two thirds of the whole text, it covers the years from the Creation to Christ’s Resurrection. The compilers complemented it with an excerpt from a common edition of the Chronicles of George Synkellos and Theophanes the Confessor, thus taking their account to the foundation of Constantinople. Created most likely in Greece, the Compilation was translated in the early 10th century in Bulgaria, during the reign of Simeon the Great, only a few decades after the nation’s conversion to Christianity. This paper analyses the periphrastic practices of the Bulgarian translators who had to adequately render the biblical and non-biblical toponyms, adapting them to the Old Bulgarian phonetics and morphology. The analysis is complicated by the fact that the Greek original of the Compilation has been lost (or has not yet been identified). In order to identify the toponyms and their meanings, the author, where appropriate, makes use of parallels from the Septuagint and the Chronicle of Synkellos. The analysis shows that the Bulgarian translator/s had a good command of Greek and a good knowledge of the biblical geography – the number of correctly translated toponyms exceeds the number of those that were misspelled (the misspellings probably occurred during the long text transmission).